2009
DOI: 10.1021/om900356w
|View full text |Cite
|
Sign up to set email alerts
|

Chelating NHC Ruthenium(II) Complexes as Robust Homogeneous Hydrogenation Catalysts

Abstract: A series of ruthenium(II) complexes have been prepared by using bidentate chelating N-heterocyclic carbene (NHC) ligands that feature different donor groups E (E=olefin, thioether, carboxylate, and NHC). Rigid coordination of all donor sites was concluded from NMR spectroscopy, and the electronic impact of the donor group was evaluated by electrochemical analyses. The chelating donor group had a strong influence on the activity of the metal center in catalyzing direct hydrogenation of styrene. A thioether grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 96 publications
3
82
0
Order By: Relevance
“…The hydrogen transfer rate increased substantially upon degassing the solvent and upon performing the reaction in a gas-tight tube under an inert atmosphere and at 90°C. Under these conditions, complete conversion was reached after less than one hour (Table 1 entry 5). No induction time was noted.…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 91%
See 2 more Smart Citations
“…The hydrogen transfer rate increased substantially upon degassing the solvent and upon performing the reaction in a gas-tight tube under an inert atmosphere and at 90°C. Under these conditions, complete conversion was reached after less than one hour (Table 1 entry 5). No induction time was noted.…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 91%
“…[15] We therefore extended our studies to the hydrogenation of other functional groups and activated C=C bonds, which were successfully converted by direct hydrogenation using complexes 1-4. [5] …”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bis-NHCs have been coordinated to many transition metals: ruthenium, 4 rhodium, 3,5 iridium, 6 palladium, 7 platinum, 8,9 and more recently also the first row metals such as nickel [10][11][12] and iron. 13,14 We are interested in the properties and reactivity of low-valent late transition metal complexes, notably electron rich zero-valent palladium NHC complexes, as these often play a vital role in the catalytic cycles of many reactions.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently observed that ruthenium complexes comprising a chelating N-heterocyclic carbene (NHC) ligand are catalyst precursors both for the direct hydrogenation of olefins 8 heating gave only a slight increase of hydrogenated product (32% dodecane after 24 h, Table 1). The activity of complex 4 was similar to that of 3 after 5 h (37% hydrogenated product, 63% dodecenes), yet hydrogenation continued and reached 79% after 24 h. Significant higher transfer activity was 55 observed for the olefin-functionalised NHC complex 1, which induced consumption of all starting material within 30 min and complete hydrogenation within 24 h.…”
mentioning
confidence: 99%